Reaching new lights: a review on photo-controlled nanomedicines and their in vivo evaluation. (25th January 2023) - Remmers, Rik C. P. A.; Neumann, Kevin
Abstract : Light emerged as one of the most powerful stimuli for controlled drug release from nanomedicines. This review discusses the chemical design and efficiency of photo-controlled nanomedicines that have been evaluated in vivo . Abstract : The selective and efficient delivery of bioactive molecules to sites of interest remains a formidable challenge in medicine. In recent years, it has been shown that stimuli-responsive drug delivery systems display several advantages over traditional drug administration such as an improved pharmacokinetic profile and the desirable ability to gain control over release. Light emerged as one of the most powerful stimuli due to its high biocompatibility, spatio-temporal control, and non-invasiveness. On the road to clinical translation, various chemical systems of high complexity have been reported with the aim to improve efficacy, safety, and versatility of drug delivery under complex biological conditions. For future research on the chemical design of such photo-controlled nanomedicines, it is essential to gain an understanding of their in vivo translation and efficiency. Here, we discuss photo-controlled nanomedicines that have been evaluated in vivo and provide an overview of the state-of-the-art that should guide future research design.